Justice and diplomacy : resolving contradictions in diplomatic practice and international humanitarian law - Ellis, Mark S.; Doutriaux, Yves; Ryback, Timothy W. (Cambridge, United Kingdom : Cambridge University Press, 2018)
Justice and Diplomacy is intended for scholars of international relations, human rights and humanitarian law, as well as practising diplomats and jurists engaged in peace negotiations in conflict regions, countries undergoing political transitions following mass atrocities, and other international situations involving suspected war crimes, crimes against humanity, or genocide.
Acountability : diplomatic negotiation and judicial process : focus: Bosnia -- Legal expertise : implications of legal terminology in diplomatic processes : focus: Rwanda -- Compliance : enforcing international arrest warrants through diplomacy : focus: Kosovo -- Timing and signaling : implications of judicial and diplomatic process : focus: Darfur -- Alignment : identifying potential alignments between diplomatic and judicial processes : focus: Libya.
Includes bibliographical references and index.
Keywords: Humanitarian intervention; Humanitarian law; International criminal law; Diplomacy